2014
DOI: 10.2134/agronj13.0542
|View full text |Cite
|
Sign up to set email alerts
|

Silage Yield and Nutritive Value of Millet–Soybean Intercrops as Influenced by Nitrogen Application

Abstract: Shortage of irrigation water in arid and semi-arid regions has forced forage producers to look for drought-tolerant species for silage production. To evaluate silage yield and nutritive value of pearl millet (Pennisetum glaucum L.)-soybean [Glycine max (L.) Merr.] intercrops as influenced by intercropping ratios and N rates, a 2-yr field experiment was conducted using split-plot lay out on a randomized complete block (RCB) design. Main plots consisted of 0, 37, and 74 kg N ha -1 (N 0 , N 37 , and N 74 , respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…While some research has indicated that increased amounts of chemical fertilizers may suppress soybean yields (Hiebsch & McCollum, 1987), in the present study, the positive response of corn to NPK (Jahanzad et al, 2014) compensated for the probable yield suppression of soybean, which ultimately resulted in the greatest forage DM yield in the 100% NPK and 50% CM+50% NPK treatments.…”
Section: Discussionmentioning
confidence: 49%
“…While some research has indicated that increased amounts of chemical fertilizers may suppress soybean yields (Hiebsch & McCollum, 1987), in the present study, the positive response of corn to NPK (Jahanzad et al, 2014) compensated for the probable yield suppression of soybean, which ultimately resulted in the greatest forage DM yield in the 100% NPK and 50% CM+50% NPK treatments.…”
Section: Discussionmentioning
confidence: 49%
“…The intercrops of millet–soya bean tended to have higher lactic acid compared with millet monoculture. As legumes have higher BC than grasses, the millet–soya bean mixtures are likely to require more acid to reach the same pH, compared with millet monocultures (McDonald et al ., ; Jahanzad et al ., ). The pH of millet–soya bean forage stabilized at a lower level when millet made up a greater proportion of the mixture.…”
Section: Discussionmentioning
confidence: 97%
“…Millet sole crop produced 15% lower protein yield compared with 60:40 millet-soybean at the same N level (Table 1). Elevated levels of CP by increased N fertilization in cereal-legume intercropping systems have been reported by other researchers (Mariotti et al, 2011;Zandvakili et al, 2012;Jahanzad et al, 2014). These results suggest that relying on soybean alone as an on-farm source of protein is not sufficient to satisfy farmer needs and that appropriate intercropping ratios can produce more CP compared with millet monoculture.…”
Section: Forage Dry Matter and Protein Yieldmentioning
confidence: 66%
“…The highest LER value was recorded from 60:40 millet-soybean at N 74 , which showed 17% higher LER compared with millet sole crop at the same fertility level (Table 2). While some studies have reported that intercropping of two or more crops may not necessarily lead to forage biomass yield improvement, higher LER in intercropping ratios has been reported in other studies (Lithourgidis and Dordas, 2010;Mariotti et al, 2011;Jahanzad et al, 2014), indicating the benefits that could be gained from intercropping cereals and legumes. An increased LER value with increasing N rates has also been reported by Zandvakili et al (2013) in sorghum-lima bean (Phaseolus lunatus L.) intercropping.…”
Section: Competition Indices and Economic Benefitmentioning
confidence: 74%
See 1 more Smart Citation